Solid cation exchange phase to remove interfering anthocyanins in the analysis of other bioactive phenols in red wine. (15th July 2017) - da Silva, Letícia Flores; Guerra, Celito Crivellaro; Klein, Diandra; Bergold, Ana Maria
Highlights: A novel sample preparation for bioactive phenol analysis in red wines is proposed. Removal of anthocyanin interferences was achieved through cation exchange. A suitable relationship between the analytes' selectivity and recoveries was found. Green chemistry principles were followed, such as solvent and column economy. The method may be extended to analyze other foods and beverages. Abstract: Bioactive phenols (BPs) are often targets in red wine analysis. However, other compounds interfere in the liquid chromatography methods used for this analysis. Here, purification procedures were tested to eliminate anthocyanin interference during the determination of 19 red-wine BPs. Liquid chromatography, coupled to a diode array detector (HPLC-DAD) and a mass spectrometer (UPLC-MS), was used to compare the direct injection of the samples with solid-phase extractions: reversed-phase (C18) and strong cation-exchange (SCX). The HPLC-DAD method revealed that, out of 13 BPs, only six are selectively analyzed with or without C18 treatment, whereas SCX enabled the detection of all BPs. The recovery with SCX was above 86.6% for eight BPs. Moreover, UPLC-MS demonstrated the potential of SCX sample preparation for the determination of 19 BPs. The developed procedure may be extended to the analysis of other red wine molecules or to other analytical methods where anthocyanins may interfere.